KMT2D regulates activation, localization, and integrin expression by T-cells - Potter, Sarah J.; Zhang, Li; Kotliar, Michael; Wu, Yuehong; Schafer, Caitlin; Stefan, Kurtis; Boukas, Leandros; Qu’d, Dima; Bodamer, Olaf; Simpson, Brittany N.; Barski, Artem; Lindsley, Andrew W.; et al. (Frontiers in Immunology, 2024)
Individuals with Kabuki syndrome present with immunodeficiency; however, how pathogenic variants in the gene encoding the histone-modifying enzyme lysine methyltransferase 2D (KMT2D) lead to immune alterations remain poorly understood. Following up on our prior report of KMT2D-altered integrin expression in B cells, we performed targeted analyses of KMT2D's influence on integrin expression in T cells throughout development (thymocytes through peripheral T cells) in murine cells with constitutive-and conditional-targeted Kmt2d deletion.Using high-throughput RNA-sequencing and flow cytometry, we reveal decreased expression (both at the transcriptional and translational level) of a cluster of leukocyte-specific integrins, which perturb aspects of T cell activation, maturation, adhesion/localization, and effector function.H3K4me3 ChIP-PCR suggestsdemonstrates these evolutionary similar integrins are under direct control of KMT2D. KMT2D loss also alters multiple downstream programming/signaling pathways, including integrin-based localization, which can influence T cell populations. We further demonstrated KMT2D deficiency is associated with the accumulation of murine CD8 + single-positive (SP) thymocytes and shifts in both human and murine peripheral T cell populations, including the reduction of the CD4 + recent thymic emigrant (RTE) population. Together these data show that the targeted loss of Kmt2d in the T cell lineage recapitulates several distinct features of Kabuki syndrome-associated immune deficiency and implicates epigenetic mechanisms in the regulation of integrin signaling.